2014
DOI: 10.1002/humu.22602
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Cellular Analysis of Human Variants of the DYT1 Dystonia Protein, TorsinA/TOR1A

Abstract: Early-onset dystonia is associated with the deletion of one of a pair of glutamic acid residues (c.904_906delGAG/c.907_909delGAG; p.Glu302del/Glu303del; ΔE 302/303) near the carboxyl-terminus of torsinA, a member of the AAA+ protein family that localizes to the endoplasmic reticulum (ER) lumen and nuclear envelope (NE). This deletion commonly underlies early-onset DYT1 dystonia. While the role of the disease-causing mutation, torsinAΔE, has been established through genetic association studies, it is much less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 82 publications
(128 reference statements)
1
22
1
1
Order By: Relevance
“…In addition to c.904_906delGAG, several missense variants (including R288Q [p.Arg288Gln; c.863G>A] and F205I [p.Phe205Ile, c.613T>A]) found in dystonia patients have been published. These 3 types of mutant proteins all show an increased tendency to dimerize as well as impaired processing and altered NE morphology . Another rare variant found in our patients (c.860C>A) is adjacent to R288Q, so if c.860C>A damages the protein, it will likely cause dystonia.…”
Section: Discussionmentioning
confidence: 71%
“…In addition to c.904_906delGAG, several missense variants (including R288Q [p.Arg288Gln; c.863G>A] and F205I [p.Phe205Ile, c.613T>A]) found in dystonia patients have been published. These 3 types of mutant proteins all show an increased tendency to dimerize as well as impaired processing and altered NE morphology . Another rare variant found in our patients (c.860C>A) is adjacent to R288Q, so if c.860C>A damages the protein, it will likely cause dystonia.…”
Section: Discussionmentioning
confidence: 71%
“…TOR1A protein, called TorsinA belongs to the family of the AAA+ ATPases that can be found in the endoplasmic reticulum and nuclear envelope of most cells [8] including cells of the central nervous system [1] and are associated with a variety of cellular activities [9]. The function of TorsinA and how TOR1A gene mutations lead to dystonia is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The function of TorsinA and how TOR1A gene mutations lead to dystonia is poorly understood. However, it seems that TorsinA is implicated in several molecular and cellular procedures, such as the interactions between cytoskeleton and membrane, important functions of the endoplasmic reticulum (reaction to stress, secretory pathway, protein degradation, neurites’ expansion) and of the nuclear envelope (membrane formation and cell migration) [1, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Rare variants in the Tor1a gene, as well as other genes associated with dystonia, have been reported in cases of sporadic dystonias (Calakos et al, 2010; Dobričić et al, 2015; Dufke et al, 2014; Groen et al, 2015; Groen et al, 2014; Hettich et al, 2014; Kock et al, 2006; Kumar et al, 2014; Lohmann et al, 2012; Nibbeling et al, 2015; Saunders-Pullman et al, 2014; Vemula et al, 2014; Vulinovic et al, 2014; Zech et al, 2014; Ziegan et al, 2014), suggesting this as one potential genetic contribution to disease. However, obtaining formal genetic support, as in association studies, is fundamentally challenged when rare genetic events occur in rare disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In prior work, we found that, similar to ΔE TorsinA, F205I TorsinA protein mislocalizes and forms inclusions when over-expressed in cultured cells, though not to as severe a degree (Calakos et al, 2010). Nery and colleagues further showed that the F205I variant disrupts ER function (Hettich et al, 2014). These observations suggest that the mutation may be pathophysiologically significant.…”
Section: Introductionmentioning
confidence: 99%